3000 proverbs - Phillips, Sam (Goodwell Publishing House New Delhi, 2012)
3000 Proverbs by Sam Phillips is a comprehensive collection of timeless wisdom from cultures around the world. Each proverb provides insight into universal truths about life, human nature, and society, offering readers valuable lessons on topics such as love, work, friendship, and morality.